Translation in Javanese Qur’an Interpretation: A Study of Al-Ibriz Interpretation by KH. Bisri Musthofa - Mohammad Nasih Al Hashas; Kamal Yusuf; Dafa Aqila Musyaffa (Jurnal test, 2025)
The purpose of this study is to identify the translation techniques and strategies used in translating the Qur’anic text into Javanese, and to assess their suitability with modern translation theories. This study uses a qualitative-descriptive approach with a content analysis method. Primary data in the form of translated quotations of Qur’anic verses in the Tafsir al-Ibriz were analyzed by comparing them with the source text and examining them based on translation techniques and strategies. Secondary data were obtained from relevant literature on translation theory and tafsir studies. The results of the study indicate that KH. Bisri Musthofa applied various translation techniques and strategies such as correspondence, explanation, expansion, reduction, substitution, borrowing, adaptation, as well as structural and semantic strategies. His translation was not solely oriented towards literal meaning, but also considered the cultural background, oral tradition, and level of understanding of Javanese readers. This proves that translating religious texts requires a balance between fidelity to the source text and acceptability in the target language. The implications of this study confirm that KH. Bisri Musthofa’s efforts are an important example in locality-based translation studies, where the Qur’an is translated while respecting the authenticity of the Arabic text while being relevant to Javanese culture. This contribution opens up space for the development of translation science and a contextual approach in conveying religious messages.